Engineering Dielectrics Volume I Corona Measurement and Interpretation 1979
DOI: 10.1520/stp37832s
|View full text |Cite
|
Sign up to set email alerts
|

Partial Discharges Under Impulse-Voltage Conditions

Abstract: Throughout this chapter, the following symbols will be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…With an appropriate filtering technique, a measuring sensitivity of up to 3pC could be achieved. It has been justified that the main discharges occur during the short period of application of the front impulse voltage, followed by small discharges with reversed polarity [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an appropriate filtering technique, a measuring sensitivity of up to 3pC could be achieved. It has been justified that the main discharges occur during the short period of application of the front impulse voltage, followed by small discharges with reversed polarity [1].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the earlier investigations mainly explored solid insulating materials [1,2,[5][6][7] and there were only a few studies that observed oil-impregnated insulation [3,8]. Consequently, many studies are still required to investigate the ageing characteristics in oil-impregnated insulation.…”
Section: Introductionmentioning
confidence: 99%